Kritik Ibn Rusyd Terhadap Pandangan Para Filsuf Tentang Ketuhanan - Sujiat Zubaidi Saleh (TSAQAFAH, 2009)
Being indirect disciple of Aristotle, Ibn Rusyd mostly studied deeply in the area of philosophy, but he also criticized frequently the view of other Muslim philosophers. Ibn Rusyd’s critics in this case are in order to purify Aristotle’s philosophy from infiltration and distorted ideas. So then he could present the philosophy of Aristotle genuinely. In this article, the writer wishes to present the analysis of Ibn Rusyd on the views of Al-Farabi, Ibn Sina and Al-Ghazali. Among the philosophers except al-Ghazali, he criticized both two from their views on the existence of God through the theory of wajib al-wujud (necessary being) and mumkin al-wujud (possible being). Ibnu Rusyd also rejected the theory on emanation of al-Farabi and Ibn Sina, because not derived from Aristotle. Ibn Rusyd concerned upon the al-Ghazalis Tahafut Al-Falasifah (Incoherence of the Philosophers) not represented all philosophers views, but the views of philosophers on Neo-Platonic which destroys the thought of Aristotle. In this point Ibn Rusyd judges, that Al-Ghazali’s criticism is incoherence.